Pengembangan Bahan Ajar pada Mata Kuliah Belajar dan Pembelajaran di Fakultas Keguruan dan Ilmu Pendidikan Universitas Batanghari Jambi - Buyung Buyung (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This study aims to develop learning and learning teaching materials. The research method used is rehabilitation and development (R & D). The development model of teaching materials used is the Dick and Carey model. This research was carried out in the Faculty of Teacher Training and Education in even semester 2017/2018. Data collection using questionnaires, interviews and observations. The results based on validation by experts were categorized as feasible with the feasibility percentage for design validation 93.33%, media validation 93.33% and 95.4% material experts. Followed by a one to one response trial there are words that are difficult to understand and use and have been corrected according to students' understanding. In the small group trial the response was good and there was no improvement. Then in the Field Trial trial (field group) received a response that the implementation of learning was smooth and enjoyable, with teaching materials that were easy to understand and in accordance with the needs of the user. From the results of Validation and trials conducted, it can be concluded that teaching and learning teaching materials are suitable for use.